The economics of the scattered green restoration in cultural landscape - H. Součková (Agricultural Economics (AGRICECON), 2003)
In this contribution, several findings from the solution of the research project QC 0266 have been summarised in a synthetic form. The project is called "Adaptation of Vegetable Growing, Fruit Growing and Flower Growing to the EU Common Market" and it deals in detail with the basic indices evolution within ornamental gardening. The aim of the output was to get data for quality incidences of the Ministry of Agriculture environmental policies and for a higher representation of the territorial systems of the ecological stability realisations in the cultural landscape of the Czech Republic.